Thermodynamics of water sorption in high performance glassy thermoplastic polymers - Scherillo, Giuseppe; Petretta, Mauro; Galizia, Michele; La Manna, Pietro; Musto, Pellegrino; Mensitieri, Giuseppe (Frontiers in Chemistry, 2014)
Sorption thermodynamics of water in two glassy polymers, polyetherimide (PEI) and polyetheretherketone (PEEK), is investigated by coupling gravimetry and on line FTIR spectroscopy in order to gather information on the total amount of sorbed water as well as on the different species of water molecules absorbed within the polymers, addressing the issue of cross- and self-interactions occurring in the polymer/water systems. Water sorption isotherms have been determined at temperatures ranging fro 30 to 70°C while FTIR spectroscopy has been performed only at 30°C. The experimental analysis provided information on the groups present on the polymer backbones involved in hydrogen bonding interactions with absorbed water molecules. Moreover, it also supplied qualitative indications about the different’populations’ of water molecules present within the PEEK and a quantitative assessment of these ‘populations’ in the case of PEI. The results of the experimental analysis have been interpreted using an equation of state theory based on a compressible lattice fluid model for the Gibbs energy of the polymer-water mixture, developed by extending to the case of out of equilibrium glassy polymers a previous model intended for equilibrium rubbery polymers. The model accounts for the non equilibrium nature of glassy poymers as well as for mean field and for hydrogen bonding interactions, providing a satisfactory quantitative interpretation of the experimental data.